A review on Single Nucleotide Polymorphism (SNPs) and their effect on cancer risk in South Asian population - Beruni, Sajid Mahmud Al (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.